Diagnostic Accuracy of Thin Film in Detection of Scanty Parasitaemia Malaria Taking Thick Film as Gold Standard - Hifza Aiman, Hira Khan, Syed Ibrahim Bukhari, Sadaf Junejo, Marium Akram, Ramchand (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Analyzing a blood film is the most accurate approach to determine the number of parasites present. People question which blood film and counting method is the most accurate and can be used again and over again. Objective: To see if thin peripheral blood smear films may identify malaria with little parasitaemia, thick peripheral blood smear films were used as the gold standard. Material and Methods: The study was conducted by the National Institute of Child Health in Karachi’s Department of Paediatric Medicine and was a cross-sectional one. 177 people were admitted to the hospital. A vein yielded about 5 milliliters of blood for the experiment. As long as there was a single control band and two testing bands, the test result was positive for both P. falciparum and P. viridans. When the control band and the test band were found to be present, the test verified the presence of P. falciparum. Results were deemed negative if neither the test nor control bands appeared. Comparison of thin peripheral blood smear accuracy to the gold standard of thick peripheral blood smear accuracy was used to assess the thin blood smear diagnostic accuracy. Results: Sixty-one percent of the patients were men, and only 39 percent were women. The average age was 30 years and 15 months. The P.falciparum was 66.0%, the P.vivax was 22.7%, and the P.ovale was 11.3%. With a thick peripheral blood smear film, 52.5 percent were found to have scanty parasitaemia malaria, and 48 percent were found to have it with a thin peripheral blood smear film. The accuracy, specificity, and sensitivity were 95.3%, 87.5%, and 90.9%, respectively. Conclusion: The results of the study showed that thin blood smear films are accurate diagnostic tools 90.9% of the time. It could be used as a second way to confirm a diagnosis of malaria.